Великий стол: роман / Д. Балашов - Балашов Дмитрий Михайлович (Репро, 2000)
Экземпляры: БС (20170227) / Инвентарный номер: РТШ49376 / Цена: 87.40 / Сис.шифр: Р2 / Авт.знак: Б 20 / ГРНТИ: 17 / ББК: 84(2)